Visitor Management of Dieng Cultural Festival and Millennial Tourist Satisfaction - Nungky Puspita; I Made Adhi Gunadi; Vinca Bunga Virananda (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2021)
Purpose: This study aimed to analyze how the management of Dieng Culture Festival attract visitors and examine the influence of Dieng Culture Festival to the millennial tourists’ satisfaction. Research methods: The methodology of this study referred to descriptive quantitative research methods. Questionnaire was used to collect the data to be analyzed using multiple linear regression analysis. Results and discussions: Satisfaction of millennial tourist can be derived from 42.6% of hard measure and soft measure variable, while the remaining 57.4% of millennial tourists’ satisfaction variables can be derived by other variables not examined in this study. Conclusion: The hypothesis test results proved that the visitor management of the Dieng Culture Festival, which use hard measure and soft measure has a significant and positive effect on millennial tourists satisfaction. Keywords: Visitor Management, Hard and Soft Measure, Tourists Satisfaction, Dieng Culture Festival